2010
DOI: 10.5301/ejo.2010.3712
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Limits of the Rebound Tonometer (ICare®): Clinical Study

Abstract: The ICare® tonometer proved to be comparable with other nonconventional tonometers and can be used by nonophthalmologists and paramedical personnel during screening tests of populations. In addition, the ICare® tonometer could be considered a valid alternative to GAT when GAT is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 25 publications
1
27
0
3
Order By: Relevance
“…Nevertheless, ICRBT overestimated IOP by 2.3 mmHg. This was similar to most of the previous studies, which reported overestimations from 0.2 to 3.4 mmHg [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently, Vasanthan Mutuvelou et al [30] showed that central ICare measurements overestimated IOP by 2 mmHg and that peripheral measurements underestimated IOP by approximately 1.4-2 mmHg.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nevertheless, ICRBT overestimated IOP by 2.3 mmHg. This was similar to most of the previous studies, which reported overestimations from 0.2 to 3.4 mmHg [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently, Vasanthan Mutuvelou et al [30] showed that central ICare measurements overestimated IOP by 2 mmHg and that peripheral measurements underestimated IOP by approximately 1.4-2 mmHg.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that the Icare tonometer provided good results in terms of ease of use, precision, and reproducibility of its measurements. It has been also shown to correlate well with GAT, even in the hands of inexperienced tonometrists [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Recently a version of the Icare tonometer (Icare ONE) for home measurement of IOP by patients became commercially available [21].…”
Section: Introductionmentioning
confidence: 99%
“…The same examiner performed all of the IOP measurements for each patient. The reliability and reproducibility of the IOP data obtained using the ICare tonometer were verified previously [26][27][28][29][30][31].…”
Section: Outcome Measuresmentioning
confidence: 60%
“…At the slit-lamp examination, the anterior segment was normal and with no signs of any ocular inflammation. His intraocular pressure (IOP) at Goldmann tonometry and iCare [4] was 17 mm Hg.…”
Section: Case Presentationmentioning
confidence: 99%